Economic and technical feasibility study of a combined-cycle cogeneration system associated with cellulose plants - Silveira, Jose Luz [UNESP]; Balestieri, José Antônio Perrella [UNESP] (My University, 1992)
In this paper, is presented an economical and technical feasibility study of a combined cycle cogeneration system proposed to be used in a pulp plant located in Brazil, where around 95% of country's pulp production is done by the use of Kraft Process. This process allows the use of black liquor and other by-products as fuel. This study is based upon actual data from a pulp plant with a daily production of 1000 tons., that generates part of the energy demanded by the process in a conventional cogeneration system with condensing steam turbine and two extractions. The addition of a gas turbine was studied to compare electricity production level and its related costs between original system and the new one, considering that the former can use industrial by-products and firewood as fuel, when required. Several parameters related to electric generation systems operation and production costs were studied. The use of natural gas in the combined cycle, in comparison with the use of firewood in the conventional system was studied. The advantages of natural gas fuel are highlighted. The surplus availability and the electricity generation costs are presented as a function of pulp and black liquor production.
Keywords: Applications; Combined cycle power plants; Energy management; Engineering research; Industrial economics; Industrial research; Kraft process; Natural gas; Paper and pulp mills; Economical and feasibility study; Cogeneration plants